2005
DOI: 10.1007/s11926-005-0018-7
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in pain responses

Abstract: The experience of pain is characterized by tremendous inter-individual variability. Indeed, an identical noxious stimulus can produce vastly different pain responses across individuals. Historically, scientists have regarded this variability as a nuisance; however, substantial data suggest that these individual differences may provide valuable information that can be used to enhance clinical management of pain. This paper discusses several factors that contribute to individual differences in pain perception, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
117
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 203 publications
(134 citation statements)
references
References 54 publications
(47 reference statements)
5
117
0
7
Order By: Relevance
“…Results from such studies have reported lower pain thresholds and tolerances among African American subjects compared to non-Hispanic white subjects across multiple experimental pain modalities. Findings from this study support and extend similar pain investigations (Fillingim 2005;Edwards et al 2003;Campbell 2004Campbell ,2005Edwards and Fillingim 1999;and Zatzick and Dimsdale 1990). Although several studies have addressed ethnic differences and pain response in clinical studies (Edwards et al 2005Green 2005Green ,2003Campbell et al 2004;Riley 2002;Greenwald 1991), and some have included multiple ethnic groups (Edwards et al 2005;Hastie, et al 2005;Watson et al 2005;Faucett et al 1994;Lawlis et al 1984;Lipton and Marbach 1984), a unique contribution of this study is the inclusion of both Hispanics and African Americans in a comparative study of experimental pain and ethnic identity.…”
Section: Discussionsupporting
confidence: 83%
“…Results from such studies have reported lower pain thresholds and tolerances among African American subjects compared to non-Hispanic white subjects across multiple experimental pain modalities. Findings from this study support and extend similar pain investigations (Fillingim 2005;Edwards et al 2003;Campbell 2004Campbell ,2005Edwards and Fillingim 1999;and Zatzick and Dimsdale 1990). Although several studies have addressed ethnic differences and pain response in clinical studies (Edwards et al 2005Green 2005Green ,2003Campbell et al 2004;Riley 2002;Greenwald 1991), and some have included multiple ethnic groups (Edwards et al 2005;Hastie, et al 2005;Watson et al 2005;Faucett et al 1994;Lawlis et al 1984;Lipton and Marbach 1984), a unique contribution of this study is the inclusion of both Hispanics and African Americans in a comparative study of experimental pain and ethnic identity.…”
Section: Discussionsupporting
confidence: 83%
“…Pain is expected after injury and surgery [3], although the extent to which patients experience pain varies [16,18,40]. Pain is the cognitive and emotional response to nociception [7,13,36].…”
Section: Introductionmentioning
confidence: 99%
“…Cultural differences in gender-specific pain patterns would suggest sociocultural mechanisms, or possibly racial differences, whereas similarities across cultures would suggest biological or biopsychological mechanisms (e.g., [181]). There is evidence that culture/race interacts with gender on the experience of pain [59,147]. Future cross-cultural studies could be useful for illuminating mechanisms underlying sex differences in pain, although cultural and genetic factors may be difficult to differentiate.…”
mentioning
confidence: 99%